2019
DOI: 10.1017/jpa.2019.20
|View full text |Cite
|
Sign up to set email alerts
|

Phyloblattidae and Compsoblattidae (Insecta, Blattodea) from the late Carboniferous Souss basin, Morocco

Abstract: The Late Pennsylvanian (Kasimovian, early Stephanian) sub- to perimontaneous Souss basin, situated in the present-day southwestern High Atlas mountains of Morocco, contains the hitherto only known late Paleozoic entomofauna from North Africa, which is simultaneously also the southernmost Euramerican entomofauna. The present study provides descriptions, identifications, and revisions of several species belonging to the genera Phyloblatta and Anthracoblattina (family Phyloblattidae) and of the genus Compsoblatta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 40 publications
(71 reference statements)
0
2
0
Order By: Relevance
“…13) and Phyloblatta , neither of which is used for biostratigraphic purposes due to their evolutionarily persistent venation patterns, weak interspecific differences, considerable individual variabilities and ecological specializations (Schneider 1978, 1983; Belahmira et al . 2019). Rather, fragments resembling the guide taxon Sysciophlebia ilfeldensis led Schneider & Werneburg (2006) to assign the Manebach Formation to what is now called the Sysciophlebia ilfeldensis – Spiloblattina weissigensis zone (Schneider et al .…”
Section: Resultsmentioning
confidence: 99%
“…13) and Phyloblatta , neither of which is used for biostratigraphic purposes due to their evolutionarily persistent venation patterns, weak interspecific differences, considerable individual variabilities and ecological specializations (Schneider 1978, 1983; Belahmira et al . 2019). Rather, fragments resembling the guide taxon Sysciophlebia ilfeldensis led Schneider & Werneburg (2006) to assign the Manebach Formation to what is now called the Sysciophlebia ilfeldensis – Spiloblattina weissigensis zone (Schneider et al .…”
Section: Resultsmentioning
confidence: 99%
“…Affinities with the Subioblattidae (Triassic) are excluded because these have the vein RP and its branches sigmoidally curved [15]. Belahmira et al [16] proposed the following diagnosis for Phyloblatta Handlirsch, 1906: 'elongate ellipsoidal forewings of about 10-35 mm in length. Costal field strip-like, up to about 70% of forewing length.…”
Section: Discussionmentioning
confidence: 99%
“…The 'Sysciophlebia praepilata' insect zone is attributed to the 'Stephanian B/C' [38] (latest Gzhelian to earliest Asselian, 303.4 to 298.9 Ma, Commentry, France). The 'Sysciophlebia euglyptica' insect zone is attributed to the 'Stephanian C' (latest Gzhelian to earliest Asselian, 303.4 to 301.2 Ma, Ottweiler Stufe Formation, Germany), while the 'Sysciophlebia ilfeldensis' and 'Sysciophlebia hercynica' insect zones are slightly younger (early-middle Asselian, 298.9 to 295.0 Ma, Ilfeld Basin, Germany) [6,19,39].…”
Section: Discussionmentioning
confidence: 99%
“…4.6). Belhamira et al (2019) indicated that the finding of Anthracoblattina in both marine and continental deposits support that these insects preferred sparsely vegetated shores of lakes and seas as habitat.…”
Section: Discussionmentioning
confidence: 96%